2007
DOI: 10.1083/jcb.200702147
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct arginine methyltransferases are required for biogenesis of Sm-class ribonucleoproteins

Abstract: Small nuclear ribonucleoproteins (snRNPs) are core components of the spliceosome. The U1, U2, U4, and U5 snRNPs each contain a common set of seven Sm proteins. Three of these Sm proteins are posttranslationally modified to contain symmetric dimethylarginine (sDMA) residues within their C-terminal tails. However, the precise function of this modification in the snRNP biogenesis pathway is unclear. Several lines of evidence suggest that the methyltransferase protein arginine methyltransferase 5 (PRMT5) is respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
116
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(124 citation statements)
references
References 33 publications
(61 reference statements)
8
116
0
Order By: Relevance
“…28,2008 PRMT5 SUPPRESSES RBL2 GENE EXPRESSION 6263 incubated in 3 ml of RPMI 1640 containing 10% FBS, and whole-cell extracts were prepared 30 h later in 100 l of radioimmunoprecipitation assay lysis buffer before PRMT5 and pocket proteins were detected by Western blotting. Primers used to generate wild-type and mutant miR-92b and miR-96 dsRNAs were described previously (30 To knock down the expression of PRMT5 and RBL2, T7-driven single-stranded DNA oligonucleotides were generated according to previously published sequences (3,15). Chromatin immunoprecipitation (ChIP) assay.…”
Section: Methodsmentioning
confidence: 99%
“…28,2008 PRMT5 SUPPRESSES RBL2 GENE EXPRESSION 6263 incubated in 3 ml of RPMI 1640 containing 10% FBS, and whole-cell extracts were prepared 30 h later in 100 l of radioimmunoprecipitation assay lysis buffer before PRMT5 and pocket proteins were detected by Western blotting. Primers used to generate wild-type and mutant miR-92b and miR-96 dsRNAs were described previously (30 To knock down the expression of PRMT5 and RBL2, T7-driven single-stranded DNA oligonucleotides were generated according to previously published sequences (3,15). Chromatin immunoprecipitation (ChIP) assay.…”
Section: Methodsmentioning
confidence: 99%
“…14,89,90 Cells lacking 5 0 -methylthioadenosine phosphorylase, a key enzyme of the methionine salvage pathway, have reduced methylation activity and coilin is re-localized to nucleoli. 91 However, this result has to be cautiously interpreted because 2 methyltransferases, PRMT5 and PRMT7, that symmetrically methylate arginines in Sm proteins, are important for snRNP biogenesis 92 and ongoing snRNP biogenesis may be critical for CB formation. 93,94 Coilin is also heavily phosphorylated and phosphorylation controls CB disassembly at mitosis, proper CB assembly after mitosis and coilin localization.…”
Section: Post-transcriptional Modificationsmentioning
confidence: 99%
“…In vivo, PRMT7 has been found to interact with the mammalian testis-specific CCTC-binding factor-like protein to control genetic imprinting (19). In addition, PRMT7 methylated the Sm proteins that constitute the spliceosome and seemed to mediate RNA splicing (20). It was also suggested that PRMT7 was associated with sensitivity to a number of DNA damage agents (21)(22)(23).…”
mentioning
confidence: 99%